THE EFFECT OF TAX COLLECTION WITH WARNING LETTER AND DISTRESS WARRANT TO TAX ARREARS DISBURSEMENT - Purwanto, Purwanto (Universitas Pendidikan Indonesia, 2017)
Abstract. The purpose of this study is to find out the effect of tax collection with warning letter and distress warrant to tax arrears disbursement in Tax Office Cimahi. The study uses descriptive method by using case study approachment. Statistical test uses multiple linear regression with SPSS software. Hypothesis testing is done by F test and T test at 5% significance level. The findings of the study are as follows: Tax collection with warning letter and distress warrant has no positive impact for both partially and simultaneously; the determination coefficient shows 0.039 which means 3.9% of tax arrears disbursement is influenced by the number of warning letter and distress warrant issued, while 96.1% of tax arrears disbursement is influenced by other factors outside of this study. This study is still relatively rare done and it is expected to contribute why the realization of tax arrears disbursement is still small. Keywords: Tax collection; Warning letter; Distress warrant; Tax arrears disbursement Abstrak. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh pemungutan pajak dengan surat peringatan dan surat tuntutan darurat terhadap pencairan tunggakan pajak di Kantor Pelayanan Pajak Cimahi. Penelitian ini menggunakan metode deskriptif dengan menggunakan pendekatan studi kasus. Uji statistik menggunakan regresi linier berganda dengan perangkat lunak SPSS. Pengujian hipotesis dilakukan dengan uji F dan uji T pada tingkat signifikansi 5%. Temuan penelitian ini adalah sebagai berikut: Pengambilan pajak dengan surat teguran dan surat paksa tidak berdampak positif baik secara parsial maupun simultan; koefisien determinasi menunjukkan 0,039 yang berarti 3,9% dari pencairan tunggakan pajak dipengaruhi oleh jumlah surat teguran dan surat paksa yang dikeluarkan, sedangkan 96,1% pembayaran tunggakan pajak dipengaruhi oleh faktor lain di luar penelitian ini. Penelitian ini masih relatif jarang dilakukan dan diharapkan dapat berkontribusi mengapa realisasi pencairan tunggakan pajak masih kecil. Kata Kunci: Penagihan pajak; Surat teguran; Surat paksa; Pencairan tunggakan pajak